An emission inventory for Cl2 and HOCl in Shanghai, 2017. (15th February 2020) - Li, Li; Yin, Sijia; Huang, Ling; Yi, Xin; Wang, Yangjun; Zhang, Kun; Ooi, Chel Gee; Allen, David T.
Abstract: Chlorine radical plays an important role in ozone formation. However, it has not generally been included in air quality modelling in China. In this study, an emission inventory for atomic chlorine precursors was developed for Shanghai in the year 2017. Total emissions of chlorine radical precursors were estimated at 8650 tons/year. The main source sectors of chlorine precursors in Shanghai include the volatilization of disinfectants, including in water treatment (850 tons/year, accounting for 9.8% among total emissions), in cooling towers (4, 000 tons/year, 46.2%), in wastewater treatment (2, 700 tons/year, 31.2%), in tap water (310 tons/year, 3.6%), in swimming pools (280 tons/year, 3.2%), and in the usage of chlorine-containing disinfectants (210 tons/year, 2.4%). The contribution of sea salt heterogeneous reactions with ozone to chlorine radical precursors is estimated as 90 tons/year; this represents a lower bound on the emissions from sea salt because of other reaction pathways (e.g., the reaction of particulate chloride with N2 O5 ). Local emissions from coal combustion and chemical manufacturing were estimated to be relatively small. This study provides a basis for further study regarding the influence of chlorine chemistry on ozone formation in Shanghai. Highlights: An emission inventory for atomic chlorine precursors was developed for Shanghai in the year 2017 for the first time. Eight source sectors of chlorine precursors are considered. It provides a basis for further study regarding the influence of chlorine chemistry on ozone formation.